Some analogues of Knopp’s core theorem - I. J. Maddox (International Journal of Mathematics and Mathematical Sciences)
Inequalities between certain functionals on the space of bounded real sequences are considered. Such inequalities being analogues of the classical theorem of Knopp on the core of a sequence. Also, a result is given on infinite matrices of bounded linear operators acting on bounded sequences in a Banach space.